(untitled) (Journal of Asian Development Studies, 2021)
Emotional intelligence is considered crucial for the leaders. School leaders in Pakistan particularly of primary schools are appointed just on the basis of seniority and the common mismanagement issues in the schools can be due to lack of emotional intelligence among them. Therefore, an effort using gender based comparative survey has been made to assess the level of emotional intelligence among primary school leaders. TEIQue has been employed to obtain data from 260 school teachers about the emotional intelligence of their school leaders. Results revealed moderate level of emotional intelligence on most of its facets among male and female school leaders. However, male school leaders have comparatively better level of EI as compared to female school leaders. The concerning authorities may timely focus to assess EI for the appointment and professional development of school leaders.